Congestion management in distribution grids using local flexibility markets: Investigating influential factors - Mehdi Attar; Sami Repo; Ville Heikkilä; Olli Suominen (International Journal of Electrical Power & Energy Systems)
The article presents findings on congestion management (CM) in distribution grids using the local flexibility market (LFM). It employs a co-simulation platform to decompose system complexity into manageable components, enabling realistic and comprehensive modeling. Through simulation, the study examines the effectiveness of flexibility in CM and the data exchange dynamics between the distribution system operator (DSO), LFM, and flexibility service provider (FSP) using a case study based on real data from a 359-bus distribution grid in Finland. Regarding flexibility effectiveness, the case study reveals that a larger BA in LFM can intensify voltage congestion, despite enhancing market liquidity. This underscores the trade-off between congestion mitigation and market liquidity, which must be carefully considered when determining BA size in LFM. The study also explores the rebound phenomenon and its negative impact on the grid, highlighting two key influencing factors: the charging/discharging inefficiency of battery storage and the grid’s operational state during rebound events. On data exchange, the article outlines key considerations for communication between the DSO, LFM, and FSP. These include message content, methods for calculating key parameters (such as BA, using sensitivity analysis), and the sequence of message exchanges between stakeholders.